Nanotechnological simulation in hydrophobic coatings for teaching - learning of chemistry from the integral professional training of SENA - Goyeneche López, Freddy
This research project was based on strengthening the theoretical-practical knowledge to apprentices in the Nanotechnological Simulation of Hydrophobic Coatings using natural, ordinary and synthetic compounds, through active and investigative pedagogical strategies carried out in the laboratory for the teaching processes- learning chemistry. Everything seeks that the apprentices learn to work with nanotechnology andits application for the use of it, in different productive and economic areas such as the primary extractive, industrial and commercial sector. A nanotechnological substance was developed through simulation based on obtaining SiO2 crystals from sea sand and its application in the hydrophobic coating for multiple surfaces in the wood, textile and glass industry. A quasi-experimental methodology was used, where the group obtainedthe induction to the design and analysis of the product to be elaborated in each of its stages, obtainingpositive general results